2020
DOI: 10.1542/peds.2020-0242i
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Pragmatic Delays for Deaf and Hard of Hearing Students in Mainstream Classrooms

Abstract: Increasingly, across the globe, deaf and hard of hearing (DHH) students are educated in mainstream schools using spoken language for communication. Classroom interactions require the use of sophisticated pragmatic language skills. Pragmatic skills can be delayed in DHH students and create challenges for the social and emotional adjustment of DHH students at school. School-aged DHH children may present to pediatric health care providers with concerns about communicating effectively and forming friendships with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…The lack of simultaneous translation was also one of the major obstacles to address [ 61 ]. Finally, delays in mainstream and remote classroom setup while interacting with deaf students or asking questions were a significant problem (since deaf students use sign language to ask questions), which the translator then interprets to the instructor [ 70 , 71 ]. The findings of Alqraini and Alasim [ 72 ] highlighted deaf students’ lack of focus during classes, as they choose to play games on their devices instead of paying attention to the ongoing lesson.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lack of simultaneous translation was also one of the major obstacles to address [ 61 ]. Finally, delays in mainstream and remote classroom setup while interacting with deaf students or asking questions were a significant problem (since deaf students use sign language to ask questions), which the translator then interprets to the instructor [ 70 , 71 ]. The findings of Alqraini and Alasim [ 72 ] highlighted deaf students’ lack of focus during classes, as they choose to play games on their devices instead of paying attention to the ongoing lesson.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, deaf students have faced emotional challenges due to isolation from their classmates and lack of access to important information during the pandemic [ 34 , 90 ]. The fact that most deaf students have experience impractical delays has also led to emotional and social issues among them [ 1 , 70 ]. All these challenges have led to numerous mental health problems and unforeseen psychological impacts [ 91 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another piece of research by Swanwick et al [35] was conducted in Ghana to determine how the pandemic had affected deaf education and found that exclusion for DHH students was different in various cultural contexts and developmental areas. Research by Paatsch and Toe [36] utilized a literature review methodology and indicated that DHH students in typical classrooms developed pragmatic skills and proposed using the conversation model to deal with the challenges faced by such students. Finally, Tomasuolo et al [37] conducted exploratory research in Italy and found that initiatives at the political and informal level promoted sign language and assisted in DHH education during the pandemic.…”
Section: Deaf Students During Covid-19 Studiesmentioning
confidence: 99%